Morphometric differences in normal bony nasolacrimal anatomy: comparison between four ethnic groups - Lin, Zhiheng; Kamath, Namita; Malik, Adeela (Surgical and radiologic anatomy, 2021)
PURPOSE: To compare bony nasolacrimal duct anatomy between ethnic groups. METHODS: A retrospective observational study of patients of four ethnic groups who had high-resolution CTs between 2004 and 2019 covering the full length of their nasolacrimal ducts in two hospitals in Essex, England. Only normal ducts were included; patients with tearing or radiological abnormalities were excluded. Measurements were taken of the nasolacrimal duct and surrounding anatomy based on measurements found in the existing literature. RESULTS: More females (n = 114) than males (n = 40) were included. South Asian (Indian subcontinent), Afro-Caribbean and European groups were equivocal demographically (n = 25-29, mean age 40-45); however, the Oriental group was fewer in number (n = 13) and slightly older (mean age 51). South Asian and European ducts had no significant differences. Afro-Caribbean ducts were wider and shorter than European. Afro-Caribbean faces are wider and their noses flatter and wider than European. Oriental ducts were wider and longer than European, but Europeans have taller noses. CONCLUSION: The results from our Oriental group fits with the published data in Orientals. The bony nasolacrimal duct is greater in calibre (inner diameter) if the patient is of Afro-Caribbean or Oriental origin compared to European or South Asian. Acquired nasolacrimal duct obstruction in Afro-Caribbean or Oriental patients may be more likely due to secondary causes.
Keywords: dospělí; senioři nad 80 let; Tomography, X-Ray Computed; Maxilla; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Young Adult; mladý dospělý; Asian People; Radiological anatomy; Nasolacrimal Duct; obstrukce slzovodu; ductus nasolacrimalis; mužské pohlaví; Adult; Adolescent; Racial Groups; ženské pohlaví; maxila; lidé; nosní skořepy; mladiství; Primary nasolacrimal duct obstruction; počítačová rentgenová tomografie; Aged; Turbinates; Asijci; senioři; Lacrimal Duct Obstruction; Male; Retrospective Studies; rasové skupiny; Female